Professional identity development in higher education: influencing factors. Issue 2 (13th March 2017) - Barbarà-i-Molinero, Alba; Cascón-Pereira, Rosalía; Hernández-Lara, Ana beatriz
Abstract : Purpose: In the last few years, the interest on professional identity development (PID) and the factors that influence PID has become central in higher education (HE) literature. However, the knowledge developed in this domain has focussed on a factor at a time and on a degree or discipline, thus being difficult to have a general picture of all the factors that influence the development of professional identity in HE. The purpose of this paper is to try to go further by proposing a systematic and integrative conceptual framework on the factors that influence PID of HE students. Design/methodology/approach: To identify the influencing factors on PID the authors used primary and secondary data sources. In particular, the authors first conducted a thorough literature review to identify the influencing factors on PID already studied, and second the authors conducted a qualitative pilot study through four Focus Groups to identify new factors not acknowledged before. Findings: The resulting integrative conceptual framework considers the following categories of influencing factors on PID: social experience, educational context, perceived congruence with the profession, demographic characteristics, professional image, professional experience, personal development and self-engagement. Research limitations/implications: The proposed framework constitutes a roadmap for future research on career development and counselling to develop in order to enhance PID at university. Nonetheless, this proposed conceptual framework needs to be validated with empirical data. Originality/value: This paper integrates all the existing knowledge on the influencing factors on PID from different disciplines by constructing a conceptual framework to be validated with further research.